A Practical Guide to the Automated Analysis of Vascular Growth, Maturation and Injury in the Brain - Rust, Ruslan; Kirabali, Tunahan; Grönnert, Lisa; Dogancay, Berre; Limasale, Yanuar D. P.; Meinhardt, Andrea; Werner, Carsten; Laviña, Bàrbara; Kulic, Luka; Nitsch, Roger M.; Tackenberg, Christian; Schwab, Martin E. (Frontiers in Neuroscience, 2020)
The distinct organization of the brain’s vasculature ensures the adequate delivery of oxygen and nutrients during development and adulthood. Acute and chronic pathological changes of the vascular system have been implicated in many neurological disorders including stroke and dementia. Here, we describe a fast, automated method that allows the highly reproducible, quantitative assessment of distinct vascular parameters and their changes based on the open source software Fiji (ImageJ). In particular, we developed a practical guide to reliably measure aspects of growth, repair and maturation of the brain’s vasculature during development and neurovascular disease in mice and humans. The script can be used to assess the effects of different external factors including pharmacological treatments or disease states. Moreover, the procedure is expandable to blood vessels of other organs and vascular in vitro models.